HUKUM ORGANISASI INTERNASIONAL SEBAGAI INSTRUMEN POLITIK DAN PENGALAMAN INDONESIA DALAM STUDI KASUS - Jennifer Fransiska Salman (Jurnal Ilmu Hukum Sui Generis, 2021)
Internasional law in its basic concept is intended to serve as legal framework for society of states.internasional law prescribes what is right and what is wrong:it also prescribes how state behaves toward one another;and it provides sanction.however,the above description is internasional law as understood in class room.in reality,internasional law is frequently used as a political instrument by states.it can be a instrument to exert pressure,instrument for intervening on other states domestic affairs without considered as violation and it can also be used to justify states’actions.The present article will describe how states have used internasional law on Indonesia as political instrument and how Indonesia have used internasional law to further national policy.